A return to spatial proximity: combining global suppliers with local subcontractors. (2015) - Grandinetti, Roberto; Tabacco, Raffaella
Over the last decades, the literature has extensively analysed the advantages of global supply networks, where spatial proximity becomes less important as a supplier selection criterion. However, in recent years a growing interest is rising on firms that are reshoring their operations, that is, moving their manufacturing back into their home countries. In this paper we aim to contribute to this field of research by analysing the partial reshoring of a firm that has recently modified the location of some of its suppliers to increase the spatial proximity with them. Our longitudinal case study suggests that the choice of increasing spatial proximity with some suppliers is the result of a process of strategic alignment of the portfolio of vertical relationships with a new business strategy that focuses on complex products characterised by a strong degree of customisation. The result of this process is a new global value chain, where global suppliers coexist with local suppliers and ICT are extensively used, deeply modifying the traditional value of spatial proximity and, thus, allowing the focal firm to act simultaneously at different spatial scales.